2021
DOI: 10.3390/foods10122943
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Features and Nutritional Value of Pig Brain: Potential and Challenges as a Sustainable Source of Nutrients

Abstract: The goal of this study was to establish the nutritional value and compositional properties of the brains of crossbred pigs (Landrace–Large white–Duroc (LLD)), in order to realize the zero-waste concept and increase the use of by-products in the sustainable meat industry. Fat (9.25% fresh weight (fw)) and protein (7.25% fw) were the principal dry matters of pig brain, followed by carbohydrate and ash. Phospholipid and cholesterol had a 3:1 ratio. Pig brain had a red tone (L* = 63.88, a* = 5.60, and b* = 15.43) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
2
8
1
Order By: Relevance
“…Among the edible viscera determined, large intestine had the highest fat content (9.85%), followed by kidney (2.28%), heart (1.16%), liver (1.12%), small intestine (0.58%) and spleen (0.47%). The present study had similar data with that of fat content of crossbred pigs of Thailand (Chanted et al, 2021). Another study reported high amount of fat content in large intestine (19.54%), followed by heart (4.55%) and lowest in spleen (0.97%) (Seong et al, 2014), which was similar with our study, even though contents were high.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 91%
See 1 more Smart Citation
“…Among the edible viscera determined, large intestine had the highest fat content (9.85%), followed by kidney (2.28%), heart (1.16%), liver (1.12%), small intestine (0.58%) and spleen (0.47%). The present study had similar data with that of fat content of crossbred pigs of Thailand (Chanted et al, 2021). Another study reported high amount of fat content in large intestine (19.54%), followed by heart (4.55%) and lowest in spleen (0.97%) (Seong et al, 2014), which was similar with our study, even though contents were high.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 91%
“…Spleen and small intestine had the highest moisture content (68.47% and 64.72%, respectively), while kidney, heart and liver had significantly lower moisture contents (61.93%, 55.25% and 50.67% respectively). Also the crossbred pigs of Thailand had high moisture content (79.96%) than the present study (Chanted et al, 2021). Another study by Seong et al, (2014), determined the proximate content in pork-by products of crossbred pigs (Landrace×Yorkshire×Duroc) of South Korea, when they found high content of moisture with an overall mean value of 76.38%.…”
Section: Proximate Compositioncontrasting
confidence: 39%
“…This is likely the result of the dominance of saturated phospholipids in the sample. As reported by others, [42] saturated lipids exist in larger percentage in porcine brain. They will co-elute with the unsaturated lipids in the same class under our TLC conditions (the R f s and shapes of the phospholipids in the lipid extracts were the same as the reference phospholipid standards) but have much lower sensitivity, therefore their presence was largely unaccounted for in our analysis.…”
Section: Application Of Cam Staining To Biological Samplessupporting
confidence: 81%
“…In actuality, some countries use high-nutrient by-products such as heart, liver, blood, lung, spleen, kidney, tripe, and brains in their cuisines [ 6 ]. Despite the fact that pig brain is a common by-product of slaughtering and pork processing, it has yet to be widely employed, particularly for human consumption [ 10 ]. Furthermore, there is no academic understanding on how to increase the value of pig brain.…”
Section: Introductionmentioning
confidence: 99%